Mental Health and Coping Patterns in Jewish Gay Men in Israel: The Role of Dual Identity Conflict, Religious Identity, and Partnership Status. Issue 7 (7th June 2018) - Zeidner, Moshe; Zevulun, Attara
ABSTRACT: This study examined the effects of dual-identity conflict, religious identity (religious/spiritual vs. sexual), and partnership status on the coping strategies and mental health of gay Jewish men in modern Israeli society. Participants were 73 religious and 71 secular gay men recruited via e-mail, social networking sites, and online resources targeting sexual minority men. Participants were assessed via measures of identity conflict, mental health, and coping strategies. Jewish gay men who reported more severe identity conflict also reported using less problem-focused and avoidance coping andmore emotion-focused coping strategies and reported poorer mental health than their less identity-conflicted counterparts. Furthermore, gay men who self-identified as religious reported poorer mental health as well as less problem-focused coping and more emotion-focused coping compared to secular men. Religious gay men in romantic relationships reported lower intensities of dual-identity conflict and better mental health compared to their nonpartnered counterparts.